P87 The Impact of Respiratory Viruses and Pulmonary Exacerbations on FEV1 Decline in Adults with Cystic Fibrosis. (19th November 2012) - Flight, WG; Mutton, KJ; Webb, AK; Bright-Thomas, RJ; Jones, AM
Abstract : Introduction: Viral respiratory infection (VRI) is associated with an increased rate of decline in lung function in children with cystic fibrosis (CF) but the long-term clinical impact of VRI in adults is poorly described. We performed a prospective observational study to determine the effect of VRI on lung function in adults with CF. Methods: 100 adults with CF were followed for 12 months. Patients were seen every two months routinely and also at onset of new respiratory symptoms. Sputum, nose- and throat-swabs were collected at each visit for virological analysis. Polymerase chain reaction assays for adenovirus, influenza A&B, metapneumovirus, parainfluenza 1–3, respiratory syncytial virus and rhinovirus were performed on each sample. Spirometry was recorded at each visit. Treatment failure was defined as a failure of the FEV1 to return to ≥90% of baseline after intravenous antibiotics. Statistical analysis utilised generalized linear models and multiple linear regression as appropriate, taking into account multiple observations from participants. Results: 191/626 (30.5%) study visits were positive for ≥1 virus with rhinovirus accounting for 72.5%. The incidence of VRI and pulmonary exacerbation (PEx) was 1.6 and 2.5 cases/patient-year respectively. VRI was associated with increased risk of PEx (OR 2.2; 95% CI 1.6 – 3.1; p<0.001). There was no significant difference in relative fall from baseline FEV1 at virus-positive compared with virus-negative visits (8.7 vs 9.4%, p=0.4). Acute fall in FEV1 was lower in virus-positive PEx compared with virus-negative PEx (12.7 vs 15.6%; p=0.04). Rate of PEx, but not of VRI, was associated with a statistically significant decline in FEV1 over one year, adjusted for age, sex and baseline lung function (β coefficient –1.79; 95% CI –3.4 to –0.2; p=0.02). Intravenous antibiotics were given for 122 PEx of which 90 had pre- and post-antibiotic FEV1 data available. 26/90 (29%) were classified as treatment failures. There was a trend towards lower likelihood of treatment failure in virus-positive PEx (OR 0.55; 95% CI 0.1 to 2.7; p=0.46). Conclusions: Incidence of PEx, but not VRI, is associated with accelerated decline in FEV1 in adults with CF. Virus-positive PEx are associated with a lower acute fall in FEV1 than virus-negative PEx.